The effects of the size of liposuction cannula on adipocyte survival and the optimum temperature for fat graft storage: an experimental study - TEZEL, ERDEM (ELSEVIER SCI LTD, 2009)
Background: Determining the most advantageous size of liposuction cannula and injection needles in terms of adipocyte viability could help to increase fat graft survival. When recurrent injections are necessary, storing fat tissue which is harvested during the first operation could be a practical solution if it is stored at an appropriate temperature providing the highest amount of viable fat cells. Methods: Fat tissue was removed from the abdomen of 10 consecutive female patients by 6-, 4- and 2-mm-diameter liposuction cannulas. Fat tissue harvested with the 6 mm cannula was injected through 14, 16 and 20 g needles and collected in separate tubes. An additional three tubes of fat samples were prepared from fat tissue obtained with the 6 mm cannula to be stored at +4, -20 and -80 degrees C for 2 weeks. Viability of the fat grafts was evaluated by fat cell isolation with collagenase digestion and staining with supravital dye and counting adipocytes with a haemocytometer. Results: The viability of fat grafts harvested with the 6 mm cannula was higher than grafts obtained with smaller cannulas. The viability of fat grafts injected through 14, 16 and 20 g needles were similar to each other. The viability of fat grafts stored at +4 degrees C was similar to fresh tissue whereas freezing fat grafts caused significant toss of viable adipocytes compared to fresh tissue. Conclusions: The use of larger liposuction cannulas for fat tissue harvesting provides more viable fat grafts. A temperature of +4 degrees C could be proposed as an effective and easily available way of storing fat grafts for at least 2 weeks. (C) 2008 British Association of Plastic, Reconstructive and Aesthetic Surgeons. Published by Elsevier Ltd. All. rights reserved.
Keywords: Fat grafts; Liposuction cannula size; Temperature of storage; ADIPOSE-TISSUE; AUTOLOGOUS FAT; SUCTION LIPECTOMY; TRANSPLANTATION; INJECTION; VIABILITY; EXPERIENCE; LIPOLYSIS; SYRINGE; HARVEST